Empowering Early Childhood Educators Through Collaborative Technology:a Drive-Based Approach to Improving Teacher Performance - Anang Setiawan; Imron Arifin; Yudhitia Dian Putra (Institut Agama Islam An-Nawawi Purworejo, 2025)
This study examines the impact of utilizing a shared Google Drive based on Belajar.ID account on improving teacher performance. The background of this study is the need to improve teachers' digital competence as part of a technology-based educational transformation. With the increasing development of digital technology, educational institutions must utilize various digital platforms to improve the quality of learning and teacher performance. This study uses a qualitative case study approach by collecting data through in-depth interviews with principals, teachers, and administrative staff and direct observation of shared Google Drive in two early childhood education institutions. The research findings show that the use of shared Google Drive facilitates administrative efficiency and encourages collaboration, knowledge sharing, and increased digital literacy among teachers. Institutional policy support, including regular training and leadership encouragement, plays an important role in ensuring the sustainability of this digital transformation. In practice, the findings of this study suggest that integrating cloud-based technology within a structured policy framework can significantly contribute to teachers' ongoing professional development.